Avaliação clínica das condições de saúde bucal de pacientes autistas - Oriqui, Maria Sílvia Younes (2006)
Autism is characterized by altered emotional and social behavior, cognitive deficiencies and lack or deficient speech. It is present at birth and is apparent by the age of three. The prevalence in the population is 1:500 though there has been an increase in the number of cases over the last decade. Data on odontologic characteristics are scarce and controversial. One example is that some authors report an increase, whilst others a reduction in respect to the rate of caries compared to normal individuals. The difficulty to perform examinations including odontologic evaluations is attributed to the behavioral disorder. The objective of this study was to evaluate the odontologic characteristics of autistic individuals and their ability to cooperate during assessment. Based on evaluation criteria for oral health created by the World Health Organization and adapted by researchers, 32 autistic individuals and 32 normal subjects from the general population, matched by gender, age, ethnic group, and social class, were evaluated. There were no significant differences in respect to the prevalence of caries or teeth submitted to any type of treatment. The autistic individuals presented with a greater number of extra-oral alterations and orthodontic problems associated with alterations in the growth of facial bones. In 90% of the cases, assessment can be achieved by dentists themselves if they adapt to the reactions of patients. Performing the exam was impossible in no cases. The results corroborate previously described reports and confirm that the oral conditions of autistic individuals are similar to the population and suggest that the greatest impediment in providing adequate oral health for these individuals seems to be in adapting the odontologic treatment to autistic behavior.